The microbial composition of the initial insult can predict the prognosis of experimental sepsis - Szabolcs Péter Tallósy (Nature Portfolio, 2021)
Abstract We hypothesized that the composition of sepsis-inducing bacterial flora influences the course of fecal peritonitis in rodents. Saline or fecal suspensions with a standardized dose range of bacterial colony-forming units (CFUs) were injected intraperitoneally into Sprague–Dawley rats. The qualitative composition of the initial inoculum and the ascites was analyzed separately by MALDI-TOF mass spectrometry. Invasive monitoring was conducted in separate anesthetized groups (n = 12–13/group) after 12, 24, 48 and 72 h to determine rat-specific organ failure assessment (ROFA) scores. Death and ROFA scores peaked at 24 h. At this time, 20% mortality occurred in animals receiving a monomicrobial E. coli suspension, and ROFA scores were significantly higher in the monomicrobial subgroup than in the polymicrobial one (median 6.5; 5.0–7.0 and 5.0; 4.75–5.0, respectively). ROFA scores dropped after 48 h, accompanied by a steady decrease in ascites CFUs and a shift towards intra-abdominal monomicrobial E. coli cultures. Furthermore, we found a relationship between ascites CFUs and the evolving change in ROFA scores throughout the study. Hence, quantitatively identical bacterial loads with mono- or polymicrobial dominance lead to a different degree of sepsis severity and divergent outcomes. Initial and intraperitoneal microbiological testing should be used to improve translational research success.